ВЛАСТЬ ВРЕМЕНИ И БЕССМЕРТИЕ ПОЭЗИИ В СОНЕТАХ ШЕКСПИРА - Курбонов Дониѐрбек Кахрамонович, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Shakespeare's sonnets are the pinnacle of English Renaissance poetry and a profound reflection on time, beauty, and love. The article analyzes how Shakespeare, drawing on the traditions of Petrarch and his English predecessors, rethinks the sonnet form, filling it with new content. The emphasis is on the theme of the destructive power of time and ways to overcome it through love and the immortal poetic word.